Household spending and fiscal support during the COVID-19 pandemic: Insights from a new consumer survey - Dimitris Georgarakos; Geoff Kenny (European Central Bank (ECB), 2022)
This paper introduces the Consumer Expectations Survey (CES), a new online, high frequency panel survey of euro area consumers' expectations and behaviour. The paper also investigates whether public perceptions about fiscal support measures introduced during the pandemic have influenced spending behaviour. We show that simple and factual information treatments about government support policies that are communicated to random subsets of respondents can help improve consumers' perceptions about the adequacy of fiscal interventions relative to the perceptions of an untreated control group. We find evidence that this improvement in beliefs has a causal effect on consumer spending, in particular raising spending on large items like holidays and cars. Moreover, we show that such beliefs also influence household expectations about own income prospects, future access to credit and financial sentiment, while they do not affect expectations about future taxes, implying no evidence of Ricardian effects in household behaviour. We find that perceptions affect spending also among households that did not receive any government support, suggesting that fiscal interventions can have broader consequences as they influence the behaviour of groups beyond the targeted ones.
Keywords: D12; E21; H31; 330; Consumer Expectations Survey; Fiscal Policy; COVID-19; Household perceptions